The potential of augmented reality in the management of restoration of heritage buildings - Bulgarelli-Bolaños, Jose Pablo (2019)
In this document, some theoretical functions are exemplified that the technology known as Augmented Reality (AR) offers to the different users that are part of the built heritage management processes. In this specific case, the first topic that is addressed is the administration of patrimonial restoration projects, followed by the potential of the AR to be used as a support tool in these processes. This is part of the Amón_RA research project: implementation of augmented reality in the enhancement of the historical urban heritage of the Amón neighborhood, registered with the Vice-Rector for Research and Extension of the Technological Institute of Costa Rica and coordinated by Dr. Arq David Porras Alfaro; as well as the proposal for the Final Project of Graduation to opt for the academic degree of Master in Project Management with Emphasis in Construction Projects entitled: “Professional management model of intervention projects of buildings with heritage declaration in Costa Rica . Case study: intervention plan of the Chapel of the Old Casa González Feo.” In this project proposal the AR is addressed as a possible support tool for the execution of the aforementioned restoration plan of the property, which has a patrimonial declaration and is located on nine street and between avenues seven and nine in the Amón neighborhood, San José. In addition, part of the experience of the executed processes of the Amón_RA project during the year 2017 and the first semester of the year 2018.